2016
DOI: 10.1016/j.pec.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring blood pressure in hypertension, patient and provider perspectives: A systematic review and thematic synthesis

Abstract: Uncertainty could be reduced by providing information specifically about how to interpret SMBP, what variation is acceptable, adjustment for home-clinic difference, and for patients what they should be concerned about and how to act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 29 publications
7
86
1
1
Order By: Relevance
“…However, a review of qualitative studies found that few patients shared this concern, and that in fact many patients felt empowered by and enjoyed self-monitoring. 24 …”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, a review of qualitative studies found that few patients shared this concern, and that in fact many patients felt empowered by and enjoyed self-monitoring. 24 …”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…48 Primary care clinicians have expressed several concerns about implementing AOBP and HBPM in a nonresearch setting: whether an AOBP/HBPM program can be efficiently incorporated into daily clinical practice; whether patients will follow through with HBPM despite its substantial time/ effort commitment; and whether patients will perform HBPM with sufficient accuracy. 14,49 With respect to the first concern about clinic efficiency, 68% of our clinic staff reported that the AOBP/ HBPM program positively affected hypertension management and did not require excessive time/ effort, an interpretation supported by the estimated time commitments noted in Table 3. While we did not objectively assess staff time commitments to the AOBP/HBPM program, 2 out of 19 respondents reported excessive time commitments of 31 to 45 minutes per patient.…”
Section: Discussionmentioning
confidence: 72%
“…Such risks have been described in patients using blood glucose and blood pressure self-monitoring devices [26,27]. Thus far, studies have suggested a decrease in adherence to EAMs over time, without mentioning the risk of addiction to physical activity data [22].…”
Section: Discussionmentioning
confidence: 99%